The Antimicrobial Peptide lin-SB056-1 and Its Dendrimeric Derivative Prevent Pseudomonas aeruginosa Biofilm Formation in Physiologically Relevant Models of Chronic Infections - Grassi, Lucia; Batoni, Giovanna; Ostyn, Lisa; Rigole, Petra; Van den Bossche, Sara; Rinaldi, Andrea C.; Maisetta, Giuseppantonio; Esin, Semih; Coenye, Tom; Crabbé, Aurélie (Frontiers in Microbiology, 2019)
Antimicrobial peptides (AMPs) are promising templates for the development of novel antibiofilm drugs. Despite the large number of studies on screening and optimization of AMPs, only a few of these evaluated the antibiofilm activity in physiologically relevant model systems. Potent in vitro activity of AMPs often does not translate into in vivo effectiveness due to the interference of the host microenvironment with peptide stability/availability. Hence, mimicking the complex environment found in biofilm-associated infections is essential to predict the clinical potential of novel AMP-based antimicrobials. In the present study, we examined the antibiofilm activity of the semi-synthetic peptide lin-SB056-1 and its dendrimeric derivative (lin-SB056-1)2-K against Pseudomonas aeruginosa in an in vivo-like three-dimensional (3-D) lung epithelial cell model and an in vitro wound model (consisting of an artificial dermis and blood components at physiological levels). Although moderately active when tested alone, lin-SB056-1 was effective in reducing P. aeruginosa biofilm formation in association with 3-D lung epithelial cells in combination with the chelating agent EDTA. The dimeric derivative (lin-SB056-1)2-K demonstrated an enhanced biofilm-inhibitory activity as compared to both lin-SB056-1 and the lin-SB056-1/EDTA combination, reducing the number of biofilm-associated bacteria up to 3-Log units at concentrations causing less than 20% cell death. Biofilm inhibition by (lin-SB056-1)2-K was reported both for the reference strain PAO1 and cystic fibrosis lung isolates of P. aeruginosa. In addition, using fluorescence microscopy, a significant decrease in biofilm-like structures associated with 3-D cells was observed after peptide exposure. Interestingly, effectiveness of (lin-SB056-1)2-K was also demonstrated in the wound model with a reduction of up to 1-Log unit in biofilm formation by P. aeruginosa PAO1 and wound isolates. Overall, combination treatment and peptide dendrimerization emerged as promising strategies to improve the efficacy of AMPs, especially under challenging host-mimicking conditions. Furthermore, the results of the present study underlined the importance of evaluating the biological properties of novel AMPs in in vivo-like model systems representative of specific infectious sites in order to make a more realistic prediction of their therapeutic success, and avoid the inclusion of unpromising peptides in animal studies and clinical trials.